Mobile App Prototype: Telemedicine for Mental Health Care During Pandemic - Jauregui-Velarde, Raul (2023)
At the end of 2019, the communicable disease COVID-19 was first detected in the city of Wuhan, China. It affected every country in the world. The Peruvian government announced quarantine and social distancing measures to prevent the spread of the virus. As a result of the measures implemented eco-nomic and social well-being of people were affected causing an increase in stress, depression and anxiety, which are emotional disorders that affect mental health. Added to this is the lack of access to mental health services. The objective is to develop a telemedicine mobile application prototype for mental health ser-vices based on android. The methodology applied was Rational Unified Process (RUP) methodology because it allows documenting, ordering and structuring software development. The result obtained was a prototype of a telemedicine mobile application with a design and functionalities that make access easy for patients and specialist to mental health services. The quality of the prototype was evaluated through the judgment of experts, who assessed its efficiency, usability and security Obtaining after the calculation, 4.66 average or mean; this indi-cates that according to the established quality range, the quality of the mobile prototype is high. In conclusion, it was possible to develop an efficient, easy-to-use and safe mobile telehealth prototype that provides a solution facilitating patient access to mental health care services for their emotional, psychological and social well-being.